2017
DOI: 10.1002/pen.24511
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of silica nanoparticles and reactive compatibilizer on the compatibilization of polystyrene/polyamide 6 blends

Abstract: This study examines the selective dispersion of nano-SiO 2 in polystyrene (PS) and polyamide 6 (PA6) blends. With the coupling assistance of 3-methacryloylpropyl trimethoxysilane (MPS), nano-SiO 2 surfaces are grafted with PS chains of different molecular weights (SiO 2 -MPS-PS) or reactive random copolymer of styrene (St) and 3-isopropenyl-a,a 0dimethylbenzene isocyanate (TMI) to produce SiO 2 -MPS-P(St-co-TMI). The isocyanate groups of the reactive copolymer can react with the terminal group of the PA6 to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Another way to compatibilize polymer blends is to selectively disperse (nano)particles to stabilize the blend. In the case of the PS/PA6 blend, different types of nanoparticles (NPs) were incorporated: montmorillonite [22], silica [23][24][25][26], TiO 2 [27], carbon nanotubes (CNT) [28]. However, it is well known that selectively dispersing micro or…”
Section: Introductionmentioning
confidence: 99%
“…Another way to compatibilize polymer blends is to selectively disperse (nano)particles to stabilize the blend. In the case of the PS/PA6 blend, different types of nanoparticles (NPs) were incorporated: montmorillonite [22], silica [23][24][25][26], TiO 2 [27], carbon nanotubes (CNT) [28]. However, it is well known that selectively dispersing micro or…”
Section: Introductionmentioning
confidence: 99%
“…In particular, methods for the polyvinyl chloride modification by polystyrene plastics and the unsaturated polyester resins modification by polyvinyl chloride have been developed . There are also known materials based on blends of polyamide 6 with polystyrene , obtained by mixing in a viscous‐flow and obtained with the use of compatibilizers and inorganic fillers , or blends of polyamide 6 with ABS . These materials have low technological shrinkage and water absorption and good performance properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have focused on effects of nanofillers on microstructure formation of immiscible blends, in recent years. It has been shown that different type nanofillers can act a compatibilizer in immiscible polymer blends due to physical interactions; mainly as the selective localization into a phase and/or interface and thus hindering the coalescence of dispersed droplets [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%